DIRAC CONFINEMENT BY A VARIATIONAL APPROACH - Tomio, L.; Ferreira, P. L. (Editrice Compositori Bologna, 1992)
An analytical approximate method for the Dirac equation with confining power law scalar plus vector potentials, applicable to the problem of the relativistic quark confinement, is presented. The method consists in an improved version of a saddle-point variational approach and it is applied to the fundamental state of massless single quarks for some especial cases of physical interest. Our treatment emphasizes aspects such as the quantum-mechanical relativistic Virial theorem, the saddle-point character of the critical point of the expectation value of the total energy, as well as the Klein paradox and the behaviour of the saddle-point variational energies and wave functions.
Keywords: OTHER TOPICS IN MATHEMATICAL METHODS IN PHYSICS; POTENTIAL MODELS; BAG MODELS AND OTHER PHENOMENOLOGICAL QUARK MODELS